Sulfhydrated Sirtuin-1 Increasing Its Deacetylation Activity Is an Essential Epigenetics Mechanism of Anti-Atherogenesis by Hydrogen Sulfide - Du, Congkuo; Lin, Xianjuan; Xu, Wenjing; Zheng, Fengjiao; Cai, Junyan; Yang, Jichun; Cui, Qinghua; Tang, Chaoshu; Cai, Jun; Xu, Guoheng; Geng, Bin (Antioxidants & redox signaling, 2019)
Hydrogen sulfide (H2S) has a protective role in the pathogenesis of atherosclerosis by multiple pathways. Sirtuin-1 ( ) is a histone deacetylase, as an essential mediated longevity gene, and has an anti-atherogenic effect by regulating the acetylation of some functional proteins. Whether is involved in protecting H2S in atherosclerosis and its mechanism remains unclear. In ApoE-knockout atherosclerosis mice, treatment with an H2S donor (NaHS or GYY4137) reduced atherosclerotic plaque area, macrophage infiltration, aortic inflammation, and plasma lipid level. H2S treatment increased aorta and liver mRNA expression. Overexpression or slicing cystathionine gamma lyase (CSE) also changed intracellular expression. CSE/H2S treatment increased deacetylation in endothelium and hepatocytes and macrophages, then induced deacetylation of its target proteins (P53, P65, and sterol response element binding protein), thereby reducing endothelial and macrophage inflammation and inhibiting macrophage cholesterol uptake and cholesterol synthesis of liver. Also, CSE/H2S induced sulfhydration at its two zinc finger domains, increased its zinc ion binding activity to stabilize the alpha-helix structure, lowered its ubiquitination, and reduced its degradation. H2S is a novel activator by direct sulfhydration. Because has a role in longevity, H2S may be a protector for aging-related diseases. Endogenous CSE/H2S directly sulfhydrated , enhanced binding to zinc ion, then promoted its deacetylation activity, and increased stability, thus reducing atherosclerotic plaque formation.